2020
DOI: 10.3390/jcm9061608
|View full text |Cite
|
Sign up to set email alerts
|

Post-Infectious Myocardial Infarction: Does Percutaneous Coronary Intervention Improve Outcomes? A Propensity Score-Matched Analysis

Abstract: Acute infection is a frequent trigger of myocardial infarction (MI). However, whether percutaneous coronary intervention (PCI) improves post-infectious MI prognosis is a major but unsolved issue. In this prospective multicenter study from coronary care units, we performed propensity score-matched analysis to compare outcomes in patients with and without PCI for post-infectious MI with angiography-proven significant coronary stenosis (>50%). Among 4573 consecutive MI patients, 476 patients (10%) had a concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our study findings are consistent with few previous studies with certain limitations [ 6 , 15 , 16 , 21 ]. Information regarding the severity of pneumonia in patients presenting to the emergency department was limited.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study findings are consistent with few previous studies with certain limitations [ 6 , 15 , 16 , 21 ]. Information regarding the severity of pneumonia in patients presenting to the emergency department was limited.…”
Section: Discussionsupporting
confidence: 93%
“…A prospective cohort examining the prognosis after PCI intervention in post-infection AMI concluded that PCI did not improve long-term prognosis. However, this study had a population with more serious comorbidities, and most patients required critical care [ 6 ]. In our analysis of 47,220 patients with AMI and pneumonia, 14.36% underwent PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations